Emapalumab for severe cytokine release syndrome in solid tumor CAR-T: a case report - Ruemmele, Tyler; Macedo, Rodney; Stein, Mark N.; Chan, Hei Ton; Mapara, Markus Y.; Jacquemont, Céline F.; Reshef, Ran (Frontiers in Oncology, 2025)
Chimeric Antigen Receptor T (CAR-T) cell therapy significantly and rapidly changed the treatment paradigm for lymphoma, myeloma and leukemia, and the recent approvals of the first cellular immunotherapies in melanoma and synovial sarcoma demonstrate the potential success of this approach in solid tumors. Though the therapeutic potential of CAR-T is impressive, severe cytokine release syndrome (CRS) remains an ongoing challenge. Here we report a patient who received an investigational CAR-T product for metastatic castration-resistant prostate cancer who developed multi-drug refractory, life-threatening CRS, which was successfully treated with the interferon (IFN)-γ antagonist emapalumab. Within 12 hours after the first dose of emapalumab, there was a dramatic improvement in hemodynamic status and the patient was weaned off all four vasopressors. The hemodynamic improvement was associated with a decrease in IFN-γ and CXCL10 levels but no other cytokines. Not only was emapalumab the only drug effective at treating this case of refractory CRS, but it did not appear to reduce the activity of the CAR-T product, as the CAR-T vector copy numbers remained persistent and the patient’s PSA levels remained low. This case demonstrates the clinical use of emapalumab to treat refractory cytokine release syndrome in a solid tumor CAR-T while potentially preserving therapeutic efficacy of CAR-T therapy. Further studies with larger patient populations are needed to evaluate the use of emapalumab as a treatment for CRS.